ANALISIS EPISTEMOLOGICAL OBSTACLE PADA MATERI PERBANDINGAN SISWA SMP KELAS VIII - Rismayantini Rismayantini; Gida Kadarisma; Euis Eti Rohaeti (IKIP Siliwangi, 2021)
This study aims to analyze the epistemological obstacle experienced by junior high school students when understanding concepts and solving problems regarding comparison material. The focus of this research is on the epistemological obstacle. The method in this research is descriptive qualitative and tested on students of class VIII - C at SMP Pasundan 3 Cimahi, totaling 34 students, the research instrument is a test instrument, namely 7 items regarding comparison material. Data processing in this study uses Microsoft Excel. The result of this research is the occurrence of an epistemological obstacle in junior high school students, namely when understanding the concept and solving a problems where there are limitations to the students in certain contexts regarding comparison material.